2012
DOI: 10.1002/yea.2909
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Candida boidinii MIG1 and its role in the regulation of methanol‐inducible gene expression

Abstract: Methanol-inducible gene promoters in methanol-utilizing yeasts are used in high-level heterologous gene expression systems. Generally, expression of methanol-inducible genes is completely repressed by the presence of glucose. In this study we identified the MIG1 gene in Candida boidinii, which encodes a homologue of the glucose repressor Mig1p of Saccharomyces cerevisiae. Disruption of the CbMIG1 gene had no growth effect on various carbon sources. Activation of the methanol-inducible AOD1 gene, which encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(47 reference statements)
0
8
1
Order By: Relevance
“…The key enzymes of methanol metabolism in methylotrophic yeasts are highly induced by methanol and are virtually absent when cells are growing on glucose. We have studied the regulation of the methanol-inducible genes necessary for methanol metabolism and characterized several transcription factors involved in their regulation in C. boidinii (8)(9)(10)(11). Based on our previous results, we have proposed three modes of regulation during methanol-inducible gene expression, that is, CbMig1p- dependent glucose repression, CbTrm2p-dependent derepression, and CbTrm1p-dependent methanol-specific induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key enzymes of methanol metabolism in methylotrophic yeasts are highly induced by methanol and are virtually absent when cells are growing on glucose. We have studied the regulation of the methanol-inducible genes necessary for methanol metabolism and characterized several transcription factors involved in their regulation in C. boidinii (8)(9)(10)(11). Based on our previous results, we have proposed three modes of regulation during methanol-inducible gene expression, that is, CbMig1p- dependent glucose repression, CbTrm2p-dependent derepression, and CbTrm1p-dependent methanol-specific induction.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we identified several transcription factors responsible for methanol-inducible gene expression in C. boidinii and revealed the specific function of each transcription factor, i.e., CbMig1p in glucose repression, CbTrm2p in glucose derepression, and CbTrm1p in methanol-specific induction (8)(9)(10)(11). Among these three modes of regulation, the molecular mechanism of glucose repression/derepression has been extensively studied in the budding yeast Saccharomyces cerevisiae after a shift of the carbon source from glucose to the nonfermentable carbon source ethanol or glycerol (12,13).…”
mentioning
confidence: 98%
“…This fact enables the use of unmodified host strains without additional deletion of typical repressors ( MIG1 and MIG2 , S 2). Since Mig1/2p homologs in S. cerevisiae and related methylotrophic yeasts (Stasyk et al, ; Zhai, Yurimoto, & Sakai, ) release glucose repression upon glucose depletion, such knockouts appear to become obsolete under derepressed conditions in P. pastoris . Once derepressed conditions are reached, overexpression of the factors appears to mimic methanol induction.…”
Section: Discussionmentioning
confidence: 99%
“…This fact enables the use of unmodified host strains without additional deletion of typical repressors (MIG1 and MIG2, S 2). Since Mig1/2p homologs in S. cerevisiae and related methylotrophic yeasts (Stasyk et al, 2007;Zhai, Yurimoto, & Sakai, 2012)…”
Section: Autoinducible Expression By Derepressed Activatorsmentioning
confidence: 99%
“…Exhaustion of glucose releases glucose repression, resulting in activation of methanol-regulated genes by CbTrm2p, which does not require methanol for gene activation (derepression). In addition, the presence of methanol induces maximum activation of methanolregulated genes via CbTrm1p (methanol induction; methanol-specific induction) (Hartner & Glieder, 2006;Sasano et al, 2008;Yurimoto, 2009;Sasano et al, 2010;Zhai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%